Nuf2 Is a Prognostic-Related Biomarker and Correlated With Immune Infiltrates in Hepatocellular Carcinoma - Xie, Xingwei; Jiang, Shanshan; Li, Xiang (Frontiers in Oncology, 2021)
Nuf2 participates in the regulation of cell apoptosis and proliferation by regulating the binding of centromere and spindle microtubules to achieve the correct separation of chromosomes. Previous reports have suggested that Nuf2 may play a role in various human cancers. However, the mechanism and function of Nuf2 in the development of Hepatocellular carcinoma (HCC) remains uncertain. This study investigated the prognostic potential of Nuf2 and its relation with immune cell infiltration in HCC. Nuf2 expression in tumor cells was examined using the TIMER and Oncomine databases, and its prognostic potential was assessed via the Kaplan-Meier plotter and GEPIA databases. The relationships between Nuf2 and tumor immune infiltration were analyzed using TIMER. The relationships between Nuf2 and biomarkers of tumor immune infiltration were analyzed using TIMER and GEPIA. Here we revealed that Nuf2 expression increased in tumor tissues containing HCC, and this correlated with poor relapse-free survival, disease-specific survival, progression-free survival, and overall survival in patients with HCC regardless of grades, genders, races, drinking behaviors and other clinical factors. Additionally, high expression of Nuf2 was positively correlated with differential immune cell infiltration and various immune biomarkers. Our work demonstrated that Nuf2 could be a potential prognostic biomarker and could be related to tumor immune cell infiltration in HCC.